The Challenge of Feminist Theology - Keightley, Georgia Masters (Horizons, 1987)
The feminist critique of theology is a radical and extensive one. This article examines contemporary feminist scholarship as it relates to three strategic issues in theological anthropology: (1) traditional interpretations of woman's nature; (2) the long-standing tendency to justify woman's social inferiority on the grounds of her "natural" inferiority; and (3) the complete oversight of the area of woman's experience. It will then be shown that this particular critique comes to a point of convergence in theological method, thus creating fundamental questions about accepted principles now directing the theologian's work.